Pengaruh Keseimbangan Kerja (Work Life-Balance) Terhadap Kepuasan Kerja Karyawan pada PT Ide Kreasi Warna - Jina Andarista; Nurdin Latif; Jumaidah Jumaidah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to examine The Effect Of Work-Life Balance On Employee Job Satisfaction at PT Ide Kreasi Warna, a company engaged in the sales of paint and building materials. The research method involved 48 respondents grouped based on demographic characteristics such as age, gender, and education level. Linear regression analysis results showed a positive relationship between work-life balance and job satisfaction, with a positive regression coefficient, indicating that a one-point increase in work-life balance would increase job satisfaction by 61.9%. The partial significance test (t-test) confirmed that work-life balance has a positive and significant effect on job satisfaction, with t_calculated (9.438) greater than t_table (1.679) and a significance value (0.00) less than 0.005. The determination coefficient shows that 75.7% of the variation in job satisfaction is influenced by work-life balance. This conclusion suggests that a good work-life balance can enhance employee job satisfaction. To improve work-life balance, the company is advised to implement programs such as family gathering events. Future research is expected to explore other factors affecting job satisfaction beyond work-life balance, given that 25.3% of the variance may still be influenced by other variables.